2021
DOI: 10.3390/agronomy11102019
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal Inoculation Effect on Sweet Potato (Ipomoea batatas (L.) Lam) Seedlings

Abstract: Sweet potato is an increasingly significant crop and its effective and sustainable cultivation has become important in temperate countries. The purpose of this pilot study was to investigate the effects of a mycorrhizal inoculum, Symbivit, and whether it could establish a symbiotic relationship with the seedlings of two sweet potato varieties (orange and purple). The effectiveness of the mycorrhizal inoculation with a sterilized substrate on the mycorrhizal parameters (F%, M%, m%, a%, A%) and physical paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Meanwhile, optimal K nutrient management strategy for sustainable and environmentally protective crop production was using KIUE genotypes in combination with appropriate soil fertilization ( Romheld and Kirkby, 2010 ). It is acknowledged that root architecture plays a fundamental role for water and nutrients uptake from soil and in turn, yield production ( Alhadidi et al, 2021 ; Caruso et al, 2021 ). Optimizing root morphology of sweet potato are effective methods guaranteeing yield production of sweet potato.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Meanwhile, optimal K nutrient management strategy for sustainable and environmentally protective crop production was using KIUE genotypes in combination with appropriate soil fertilization ( Romheld and Kirkby, 2010 ). It is acknowledged that root architecture plays a fundamental role for water and nutrients uptake from soil and in turn, yield production ( Alhadidi et al, 2021 ; Caruso et al, 2021 ). Optimizing root morphology of sweet potato are effective methods guaranteeing yield production of sweet potato.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that soil and rhizosphere microbial activities are the major factors that determine the availability of nutrients to plants and consequently have significant influences on root growth and plant productivity ( Wang et al, 2017 ). Recent evidence suggests that fertilization optimization and microbial inoculation were effective tools for sweet potato cultivation ( Minemba et al, 2019 ; Alhadidi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations